2019
DOI: 10.3847/1538-4357/aaf3a4
|View full text |Cite
|
Sign up to set email alerts
|

Confirming the Presence of Second-population Stars and the Iron Discrepancy along the AGB of the Globular Cluster NGC 6752

Abstract: Asymptotic giant branch (AGB) stars in the globular cluster NGC6752 have been found to exhibit some chemical peculiarities with respect to the red giant branch (RGB) stars. A discrepancy between [FeI/H] and [FeII/H] (not observed in RGB stars) has been detected adopting spectroscopic temperatures. Moreover, a possible lack of second-population stars along the AGB was claimed. The use of photometric temperatures based on (V-K) colors was proposed to erase this iron discrepancy. Also, ad hoc scenarios have been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As noted in Section 3, 6...376 is an asymptotic giant branch (AGB) star. There has been much discussion in the literature about differences in the abundances of stars on the AGB versus those on the RGB in globular clusters (Norris et al 1981;Campbell et al 2013Campbell et al , 2017MacLean et al 2016MacLean et al , 2018, in particular with respect to apparent differences in their derived metallicities and light element abundances (Lapenna et al 2016;Mucciarelli et al 2019). There are two related effects that are causing these discrepancies.…”
Section: Abundances On the Asymptotic Giant Branchmentioning
confidence: 99%
“…As noted in Section 3, 6...376 is an asymptotic giant branch (AGB) star. There has been much discussion in the literature about differences in the abundances of stars on the AGB versus those on the RGB in globular clusters (Norris et al 1981;Campbell et al 2013Campbell et al , 2017MacLean et al 2016MacLean et al , 2018, in particular with respect to apparent differences in their derived metallicities and light element abundances (Lapenna et al 2016;Mucciarelli et al 2019). There are two related effects that are causing these discrepancies.…”
Section: Abundances On the Asymptotic Giant Branchmentioning
confidence: 99%
“…Note thatCampbell et al (2013; see alsoCampbell et al 2017) claimed that all stars of second generation (i.e., with [Na/Fe] < 0.2; seeGratton et al 2012 for a review) skip the AGB. However, this result has been challenged by synthetic HB simulations(Cassisi et al 2014), and by both spectroscopic(Lapenna et al 2016;Mucciarelli et al 2019) and photometric observations(Gruyters et al 2017) that found evidence of both firstand second-generation stars along the AGB of NGC 6752.…”
mentioning
confidence: 99%
“…All observations should be of red giant branch (RGB) stars -no asymptotic giant branch (AGB) stars, horizontal branch/red clump stars, subgiants, or main sequence stars are used. RGB stars and AGB stars are the brightest stars in an old stellar population, so the most likely to be observed spectroscopically, but have different atmospheres and so their temperature and surface gravity scales may differ; moreover, the current generation of AGB model atmospheres appear to have fundamental issues that prevent consistent abundance measurements (Mucciarelli et al 2019). The relatively small range in effective temperature and surface gravity on the upper RGB dramatically reduces the likelihood of artificial inflation of abundance spreads by any residual systematic trend between them and abundance.…”
mentioning
confidence: 99%